Making Development More Sustainable? The EU Cohesion Policy and Socio-Economic Growth of Rural Regions in Poland - Dudek, Michał; Wrzochalska, Agnieszka (European Journal of Sustainable Development, 2017)
Currently one of the most widely discussed issues is the economic disparities. In order to alleviate developmental differences, a public aid is often allocated to the peripheral or less developed rural regions. The latter type of areas has long been of particular interest to the European Union (EU) and its cohesion policy. The aim of the paper was to analyse the changes in the level of socio-economic development of Polish regions in the context of cohesion policy introduction. It follows from the research that EU cohesion policy instruments contributed to the socio-economic development of regions in Poland. In the analysed time span a significant support from the EU funds was allocated to the rural regions. However, this financial aid only partly affected the reduction of socio-economic disparities in the country. The research was based on data from public statistics aggregated at the subregional level (NUTS-3) and the literature of the subject. For the purposes of this study, the method of statistical analysis was used. Keywords: rural regions, socio-economic development, EU, Cohesion Policy